Growth promotion and root colonisation in pepper plants by phosphate‐solubilising Chryseobacterium sp. strain ISE14 that suppresses Phytophthora blight. (9th February 2018) - Sang, M.K.; Jeong, J.‐J.; Kim, J.; Kim, K.D.
Abstract: Previously, we selected bacterial strain ISE14 through a sequential selection procedure that included radicle, seedling, and in planta assays and field tests. This strain not only suppressed a destructive soilborne disease, Phytophthora blight, caused by Phytophthora capsici but also increased fruit yields of pepper plants in the fields. This study was conducted to identify strain ISE14 by 16S rRNA gene sequence analysis and to characterise biocontrol and plant growth promotion activities of the strain in pepper plants. Strain ISE14, identified as Chryseobacterium sp., significantly reduced disease severity in plants inoculated with Ph. capsici and promoted plant growth (lengths and dry weights of shoots and roots) compared with those in plants treated with Escherichia coli DH5α (negative control) or MgSO4 solution (untreated control). This strain effectively colonised pepper plant roots as assessed by bacterial population analysis and confocal laser scanning microscopy; it enhanced soil microbial activity and biofilm formation, but not the production of indole acetic acid. Strain ISE14 also solubilised organic or inorganic phosphate by production of acid and alkaline phosphatases or reduction in pH, resulting in enhanced pepper plant growth. This strain exhibited similar or greater activity in disease control and plant growth promotion tests compared with positive control strains Paenibacillus polymyxa AC‐1 (biocontrol) and Bacillus vallismortis EXTN‐1 (plant growth). Therefore, Chryseobacterium sp. ISE14 may be a phosphate‐solubilising and plant growth‐promoting rhizobacterium (PGPR) strain that suppresses Phytophthora blight of pepper. To our knowledge, this is the first report of a phosphate‐solubilising PGPR strain of Chryseobacterium sp. that suppresses the pepper disease. Abstract : Confocal laser scanning micrographs of pepper (cv. 'Nockwang') roots colonised by gfp ‐tagged bacterial strains: (a) Escherichia coli DH5α (negative control); (b) Bacillus vallismortis EXTN‐1 (positive control for plant growth); (c) Paenibacillus polymyxa AC‐1 (positive control for biocontrol); and (d) Chryseobacterium sp. ISE14 at 0, 3 and 7 days after treatment (DAT) in a gnotobiotic system. No green fluorescence was observed in roots treated with 10 mM MgSO4 solution (untreated control).